2016
DOI: 10.1002/anie.201511601
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Small‐Molecule Inhibition of an Anticancer Therapeutic Protein‐Protein Interaction Using a Solid‐State Nanopore

Abstract: Nanopore sensing is an emerging technology for the single-molecule-based detection of various biomolecules. In this study, we probed the anticancer therapeutic p53 transactivation domain (p53TAD)/MDM2 interaction and its inhibition with a small-molecule MDM2 antagonist, Nutlin-3, using low-noise solid-state nanopores. Although the translocation of positively charged MDM2 through a nanopore was detected at the applied negative voltage, this MDM2 translocation was almost completely blocked upon formation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…In our previous study, the PPI between p53TAD and MDM2 was probed using a solid-state nanopores. 16 Although low-noise solid-state nanopores with pyrex substrate were used for PPI detection, they showed a relatively poor I RMS noise level ($10 pA) compared to that of aerolysin nanopore (1-1.5 pA in this study). Since intrinsically disordered p53TAD showed relatively poor signal-to-noise characteristics, we engineered the protein by tagging globular-shaped GST to enhance the sensitivity.…”
Section: Aerolysin Nanopore-based Detection Of Ppi Inhibition By Smalmentioning
confidence: 60%
See 1 more Smart Citation
“…In our previous study, the PPI between p53TAD and MDM2 was probed using a solid-state nanopores. 16 Although low-noise solid-state nanopores with pyrex substrate were used for PPI detection, they showed a relatively poor I RMS noise level ($10 pA) compared to that of aerolysin nanopore (1-1.5 pA in this study). Since intrinsically disordered p53TAD showed relatively poor signal-to-noise characteristics, we engineered the protein by tagging globular-shaped GST to enhance the sensitivity.…”
Section: Aerolysin Nanopore-based Detection Of Ppi Inhibition By Smalmentioning
confidence: 60%
“…Biological nanopores have been extensively utilized for diverse analyses of biomolecules such as nucleic acid sequencing, [4][5][6] characterization of structured oligonucleotides and biomolecular interactions, 7-10 detection of protein interaction, 11,12 and peptide sensing. 13,14 Despite previous attempts at analyzing ATCR-NCBD and p53-MDM2 interactions with solidstate nanopores, [15][16][17] there have been limitations in the application of biological nanopores for PPI analysis. Most of biological nanopores used for protein detection (such as ClyA, 18 MspA, 19 and FraC 20 ) are composed of a vestibule and a channel including the constriction region.…”
Section: Introductionmentioning
confidence: 99%
“…The On the other side, drug screening based on solid nanopore is a research hotspot but also challenging. Chae et al designed a protein complex structure to examine the interaction of mouse double minute 2 protein (MDM2) and globular glutathione-S-transferase tagged p53TAD (GST-p53TAD) [87]. p53 is an important kind of tumor suppressor protein, which can be inhibited by MDM2 via a direct interaction with the p53 transactivation domain (p53TAD).…”
Section: Of 23mentioning
confidence: 99%
“…In 2013, Freedman et al [101] detected the interactions between gp120 and its antibody, differentiating monovalent and multivalent binding of gp120 and anti-gp120 antibody based on electrical measurements. In addition, Kim's group [102,103] carried out several studies on the interactions between p53 transactivation domain (p53TAD) and mouse double minute 2 (MDM2). Via separate detection of the translocation signals of p53TAD and MDM2, it was found that the two proteins possess opposite electrical charges in neutral buffer, but the MDM2-p53TAD complex was negatively charged (Fig.…”
Section: Protein-protein Interactionsmentioning
confidence: 99%